IMPROVING PANCASILA EDUCATION LEARNING OUTCOMES THROUGH THE THINK-PAIR-SHARE MODEL IN ELEMENTARY SCHOOL - Aulia Ulva Tri Anjani (Teaching and General Education Studies, 2026)
Learning outcomes in Pancasila Education at the elementary level often remain below expectations due to teacher-centered learning, limited student engagement, and students’ difficulties in understanding abstract concepts such as the meaning of Pancasila principles in daily life. Many students tend to be passive, easily distracted, and lack motivation when learning Pancasila Education, which contributes to low comprehension and achievement. To overcome these challenges, an interactive and collaborative learning model such as Think–Pair–Share (TPS) is needed. TPS provides opportunities for students to think independently, discuss ideas with a partner, and share their understanding with the class, making it suitable for improving active participation and conceptual understanding. This study aims to determine the effectiveness of the Think–Pair–Share learning model in improving students’ learning outcomes in Pancasila Education. The research employed a quantitative approach with a pre-experimental one-group pretest–posttest design. The subjects were 25 fourth-grade students at SD Negeri 47 Lubuklinggau. Data were collected through tests (pretest and posttest), classroom observation, and documentation. The results show a significant improvement in students’ learning outcomes after the implementation of TPS. The pretest average score was 59.00, while the posttest average increased to 80.00, indicating substantial enhancement in students’ comprehension of the material “The Meaning of Pancasila Principles in Society.” In conclusion, the Think–Pair–Share model is effective in improving learning outcomes in Pancasila Education and serves as a suitable alternative learning strategy to promote active engagement and collaborative thinking among elementary school students.